2012
DOI: 10.1021/nn2043803
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Geometry, Porosity, and Surface Characteristics of Silica Nanoparticles on Acute Toxicity: Their Vasculature Effect and Tolerance Threshold

Abstract: Silica nanoparticles (SiO2) are widely used in biomedical applications such as drug delivery, cell tracking and gene transfection. The capability to control the geometry, porosity, and surface characteristics of SiO2 further provides new opportunities for their applications in nanomedicine. Concerns however remain about the potential toxic effects of SiO2 upon exposure to biological systems. In the present study, the acute toxicity of SiO2 of systematically varied geometry, porosity and surface characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
158
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(160 citation statements)
references
References 35 publications
2
158
0
Order By: Relevance
“…However, recent studies demonstrated their potential in vitro and in vivo toxicity, especially when their size is reduced to the nano scale. 3,4 Although the toxicity of silica based nanomaterials depends on several factors including particle size, shape, surface chemistry and porosity, [5][6][7] there is a general consensus that chemical structure of the surface is the predominant factor which determines the interactions with biological systems. 8 The surface of bare silica is covered with negatively charged silanol groups, which can electrostatically interact with positively charged tetraalkylammonium moieties of the cell membrane and can lead to cytotoxicity by membranolysis or inhibition of cellular respiration.…”
mentioning
confidence: 99%
“…However, recent studies demonstrated their potential in vitro and in vivo toxicity, especially when their size is reduced to the nano scale. 3,4 Although the toxicity of silica based nanomaterials depends on several factors including particle size, shape, surface chemistry and porosity, [5][6][7] there is a general consensus that chemical structure of the surface is the predominant factor which determines the interactions with biological systems. 8 The surface of bare silica is covered with negatively charged silanol groups, which can electrostatically interact with positively charged tetraalkylammonium moieties of the cell membrane and can lead to cytotoxicity by membranolysis or inhibition of cellular respiration.…”
mentioning
confidence: 99%
“…Considering their biocompatibility, SNPs have been also employed as carriers for NIR dyes for in vivo imaging of mouse bladder (Burns et al, 2009), and for specific tumor imaging (Benezra et al, 2011). The main factors which affect the acute toxicity of SNPs include shape, porosity and their surface characteristics (Nakamura et al, 2007, Yu et al, 2012. These latter affect also the colloidal stability of nanosystems in vivo, which might agglomerate and determine an immune response.…”
Section: In Vivo Optical Sensingmentioning
confidence: 99%
“…4 Briefly, 1.0 g of cetyltrimethylammonium bromide was dissolved in 500 mL of distilled water containing 3.5 mL of 2 M NaOH, and the solution was heated to 80°C. Next, 5.0 mL of tetraethylorthosilicate was added to the mixture.…”
Section: -Based Msnsmentioning
confidence: 99%
“…Numerous studies of the biocompatibility and toxicity of MSNs have been reported. [1][2][3][4] MSNs have a high surface area and large pore volumes for pay loading of magnetic centers and tunable particle size for efficient cellular uptake. [5][6][7][8][9][10][11] There has been interest in developing smart MSN nanocarriers with external and internal surfaces that can be selectively functionalized with multiple groups.…”
Section: Introductionmentioning
confidence: 99%